2006
DOI: 10.1016/j.icesjms.2006.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and ecological effects of salmon farming on wild salmon: modelling from experimental results

Abstract: O. 2006. Genetic and ecological effects of salmon farming on wild salmon: modelling from experimental results. À ICES Journal of Marine Science, 63: 1234e1247. Cultured salmonids are released or escape into the wild in large numbers and may make up significant proportions of wild salmonid populations in fresh-and saltwater, causing considerable concern for the fitness and productivity of these populations. This paper focuses on the effects of escaped farmed Atlantic salmon (Salmo salar) on wild salmon. Farmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
198
2
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(209 citation statements)
references
References 62 publications
(92 reference statements)
5
198
2
4
Order By: Relevance
“…Vectors for the transport of invasive marine or freshwater species (Kerr et al 2005) include the ballast water of barges or ships (Chesapeake Bay Commission 1995, ICES 2002, the hulls of the same (Minchin & Gollasch 2003), transfer via towing of oil and gas platforms to new sites (Hicks & Tunnell 1993), accidental release of exotic species from mariculture operations (Sapota 2004), and deliberate release of exotics by aquarium hobbyists (Weidema 2000, Christmas et al 2001, Hindar et al 2006. Recent concern regarding invasive marine species has focused on those in the Gulf of Mexico (GOM) (Osman & Shirley 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Vectors for the transport of invasive marine or freshwater species (Kerr et al 2005) include the ballast water of barges or ships (Chesapeake Bay Commission 1995, ICES 2002, the hulls of the same (Minchin & Gollasch 2003), transfer via towing of oil and gas platforms to new sites (Hicks & Tunnell 1993), accidental release of exotic species from mariculture operations (Sapota 2004), and deliberate release of exotics by aquarium hobbyists (Weidema 2000, Christmas et al 2001, Hindar et al 2006. Recent concern regarding invasive marine species has focused on those in the Gulf of Mexico (GOM) (Osman & Shirley 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that overexploitation in fisheries can induce a rapid loss of genetic variation of target species, which may diminish the adaptability and persistence of the species (Hauser et al 2002;Hutchinson et al 2003;Smith et al 1991;Turner et al 2002). A lack of a policy regarding farming industries can result in introgression of non-native or domesticated genes into wild populations, potentially causing a loss in genetic variability (Bekkevold et al 2006;Fleming et al 2000;Hindar et al 2006;McGinnity et al 2003). Investigating genetic diversity and population structure of species, after overexploitation and/or introgression have occurred, fails to maximize the potential for using this knowledge as a tool to aid in the development of policy which adequately protects biodiversity in the wild populations from anthropogenic influences.…”
Section: Introductionmentioning
confidence: 99%
“…However, the actual number of escapes is difficult to ascertain and is probably much greater than the number reported (Baarøy et al 2004, Skilbrei & Wennevik 2006. Meanwhile, both the freshwater and marine catches of Atlantic salmon in Norway are breaking low level records yearly (Statistics Norway 2010), with escaped farmed salmon making up 20 to 75% of the resident 'wild' population in some areas (Lund et al 1991, Hansen et al 1999, Fiske et al 2001, Youngson et al 2001, Carr & Whoriskey 2006, Hindar et al 2006, Erkinaro et al 2010. The reduction in the genetic differentiation of wild Atlantic salmon Salmo salar L. due to genetic mixing with farmed escapesin some cases reported to be as high as 70% -may be driving some native spawning populations to extinction (Hutchings 1991, Mork 1991, McGinnity et al 2003, Ford & Myers 2008.…”
Section: Introductionmentioning
confidence: 99%